MAPPING OF THE LOCI CONTROLLING THE RESISTANCE TO PYRENOPHORA TERES F. TERES AND COCHLIOBOLUS SATIVUS IN TWO DOUBLE HAPLOID BARLEY POPULATIONS - O. S. Afanasenko; A. V. Koziakov; P. Hedlay; N. M. Lashina; A. V. Anisimova; O. Manninen; M. Jalli; E. K. Potokina (Вавиловский журнал генетики и селекции)
Net blotch of barley (Hordeum vulgare L.), caused by Pyrenophora teres f. teres, and spot blotch, caused by Cochliobolus sativus, are the most widespread and harmful diseases in the geographic range of the crop. Barley breeding for resistance to these diseases should employ a large genetic diversity. The 11_11067 SNP marker was revealed on chromosome 6H position 58 cM in double haploid (DH) population A developed by crossing of the Ethiopian accession c-23874, highly resistant to P. teres f. teres, to the susceptible Pirkka cultivar. It was reliably (р < 0.05) associated with resistance to three P. teres f. teres isolates. In population B (Zernogradsky 813 (MR to C. sativus) × Ranniy 1 (MR to P. teres f. teres), 11 QTLs controlling resistance to 12 P. teres f. teres isolates were found on all barley chromosomes and 14 QTLs for resistance to 12 C. sativus isolates, on all chromosomes except for 4H. For both pathogens, the revealed QTLs were shown to be isolate-specific. The majority of the loci detected were mapped in the same intervals between SNP markers where QTLs controlling resistance to P. teres f. teres and C. sativus had been found by other scientists. Four novel QTLs controlling resistance to P. teres f. teres were found on chromosomes 1H, 4H, and 5H. Five novel QTLs associated with resistance to C. sativus were found on chromosomes 2Н, 3Н, 5Н, and 6Н in DH population B.